PERANAN KEHADIRAN TERHADAP KEDISIPLINAN PEGAWAI DINAS KESEJAHTERAAN SOSIAL KABUPATEN KUTAI TIMUR - Hariyati, Tati (PREDIKSI, 2016)
The purpose of this study was to determine the role of presence in the attendance book to discipline members of Aceh in the Department of Social Welfare in the East Kutai Sangata meaning high and low employee discipline allegedly caused the attendance at attendance book that is applied in the office. Therefore, researchers hypothesized, namely